A quest for Islamic learning: essays in memory of Professor Serajul Haque - Haque, Serajul; Akhtaruzzaman, Md. (Asiatic Society of Bangladesh, 2011)
Commemoration volume published in honour of Professor Serajul Haque, one of the founding leaders of Asiatic Society of Bangladesh